The Role of Agriculture in the UN Climate Talks - Campbell, Bruce M.; Wamukoya, George; Kinyangi, James; Verchot, Louis V.; Wollenberg, Eva Karoline; Vermeulen, Sonja J.; Minang, Peter A.; Neufeldt, Henry; Vidal, Alain; Loboguerrero Rodriguez, Ana María; Hedger, Merylyn (2014)
Agriculture, and consequently food security and livelihoods, is already being affected by climate change, according to latest science from the IPCC. The various strands of work already underway on agriculture within the UNFCCC process can be strengthened and made more coherent. A 2015 climate agreement should reference food production and provide the financial, technical and capacity building support for countries to devise ambitious actions for the agricultural sector. A new climate agreement should be consistent with the Sustainable Development Goal (SDG) process